THE DISCIPLINARY CULTURE OF CITATION IN SCIENTIFIC ARTICLES IN THE HUMANITIES - Komesu, Fabiana [UNESP]; Assis, Juliana Alves; Donahue, Christiane (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2023)
This article aims to identify and analyze aspects that are not dealt with or cannot be visualized in the bibliometric indexes of journals and articles in the Humanities, specifically in the field of Linguistics. This study is based on a data set of the “citing texts” (114) of three articles of the field of Linguistics that come from a Brazilian journal, a Chilean journal and a South African journal, among the most cited articles of the journals Scielo basis (Google Scholar data) in the month of September, 2021. The methodological procedures take into account the criteria (i) year of publication of the citing texts, (ii) language of publication of the citing texts, (iii) discourse genre of the citing texts, and (iv) location of the institution to which the author(s) of the citing texts are affiliated. The results problematize a culture restricted to bibliometric indexes.
LA CULTURA DISCIPLINARIA DE LAS CITAS EN LOS ARTÍCULOS CIENTÍFICOS DE HUMANIDADES
A CULTURA DISCIPLINAR DA CITAÇÃO EM ARTIGOS CIENTÍFICOS NAS HUMANIDADES
Keywords: Citation indexes; Linguistics; Literacy; Writing